Implementation of Agile Method in Employee Attendance Information Systems - Andha Maulana; Arya Yendri Pratama; Dhea Ananda; Fathan Surya Hamdi; Nabila Fadia Aqilla; Yulia Merry Anjani; Muhammad Luthfi Hamzah (Yayasan Pendidikan Islam Al-Matani, 2023)
Employee attendance is a record of a person's attendance time in a document that is properly prepared as a reference in making decisions within the scope of research. In Perhentian Marpoyan Village, the employee attendance system used is still manual, which can lead to loss or damage of existing data, lack of efficiency and effectiveness in data processing, and inaccuracies in the data. Based on these problems, a Web-based Employee Attendance Information System was created at Perhentian Marpoyan Village. The method that researchers use to create this system is the Agile Development method and uses OOAD (Object Oriented Analysis Design) modeling. This web-based employee attendance information system will be able to provide convenience in the employee attendance process, search for attendance data and minimize loss and errors in recording attendance data at Perhentian Marpoyan Village.